Effects of action relations on the configural coding between objects. - Riddoch, M; Pippard, B; Booth, L; Rickell, J; Summers, J; Brownson, A; Humphreys, G (2011)
Configural coding is known to take place between the parts of individual objects but has never been shown between separate objects. We provide novel evidence here for configural coding between separate objects through a study of the effects of action relations between objects on extinction. Patients showing visual extinction were presented with pairs of objects that were or were not co-located for action. We first confirmed the reduced extinction effect for objects co-located for action. Consistent with prior results showing that inversion disrupts configural coding, we found that inversion disrupted the benefit for action-related object pairs. This occurred both for objects with a standard canonical orientation (e.g., teapot and teacup) and those without, but where grasping and using the objects was made more difficult by inversion (e.g., spanner and nut). The data suggest that part of the affordance effect may reflect a visuo-motor response to the configural relations between stimuli. Experiment 2 showed that distorting the relative sizes of the objects also reduced the advantage for action-related pairs. We conclude that action-related pairs are processed as configurations.